HikariNeko Sdn. Bhd / Nur Hafizah Mohamad Sahabuddin - Nur Hafizah, Mohamad Sahabuddin (2020)
My business is conceptually stylish, but simple and looks rich so I use international languages such as Japanese as my company and my product name.I created a business like this because most women 's pads are designed to be uncomfortable and unsafe as they are made of waste materials such as paper and chemicals like plastic.That is why I created the company mission is "We will strive to ensure that our customers are satisfied with the commitment and attitude we give to our customers and ensure that our products are quality products and guarantee customer satisfaction" and the vision is "To create a better everyday life for the many people. " because it is based on my company's opening factors.HikariNeko sells and provides a wide range of products and services. Our top priority product is Akaichi Pad. Akaichi Pad is very special as it contains negative ion gels which can bleed. HikariNeko also provides language-friendly, polite agents and caliber.The service we place on the Akaichi Pad is a demonstration service of 'How to wash the Akaichi Pad and the advantages and differences between Akaichi Pad and other brand pads'. Then,I will introduce my reliable workers,Administrative Manager Nur Athirah Bt Aznan,Marketing Manager Nur Farisha Shahirah Bt Shahrul Azmi,Operation Manager Nurul Syahirah Bt Muhd Rashidi, Production Worker Syafiqah Bt Mohamad,Finance Manager Admirol Haqimie Bin Mohd Fauzi.I put my salary in line with the position they were in.My target audience is mainly for women between the ages of 12 and 50. It's because my company is young, so I only focused on sales in Kuala Lumpur and Selangor.After calculations, only 4% of contacts became customer base in both areas.Since the other brand pads cost RM15 - RM19 and are expensive though made from waste so I put RM26 for one Akaichi Pad in all sizes.So based on the difference in the price of other brands and my brand, my profit is only 16% of the uniqueness of this pad.Like people say ‘it is expensive as long as it is quality’. HikariNeko will use the distribution method from Manufacturer to Stockists to Consumer as its main distributor.HikariNeko uses modern methods to expand the business and popularity of Akaichi pads. Promote products through advertising on social media such as Instagram and Youtube, radio, internet (Website), business cards and television.Promotional sales methods such as P.O.P, premiums, sweepstakes and samples. Public relations benefits such as charity,a Q&A interview with the founder,share news about the jobs I creating,enter and win awards and look for awareness days relevant to my business.My last method of marketing strategy was personal selling like face-to-face demonstrations with customers.Producing intimacy products like this is extremely challenging as it involves women's vital assets, so it must be carefully and neatly made. Additionally, such intimate products have been widely marketed by other brands.However, it is an advantage because 90% of intimate brand products are designed to be unsafe to use, so many of these brand products can be studied where the disadvantages and advantages and how they work well without any problems and what materials can be added to in the manufacture of pads so that it solves the main problem of women.As I mentioned earlier, I raise prices so I only get 16% profit on every Akaichi Pad sale.I think this price is in line with the materials, the way they are made and how the packaging is designed.With such major products as the capital I need to spend is not as much as other companies / dealers because Akaichi Pad only requires certain machines such as cutters, glue machines, box makers and printers for its font and color parts.